The Barriers to Workplace Learning Implementation - Vannasy, Vanmany; Sengsouliya, Souksakhone (Universitas Pendidikan Indonesia (UPI), 2023)
Inquiry into barriers to workplace learning implementation is ongoing. This paper uses qualitative content analysis to investigate possible barriers hindering workplace learning in higher education. The study involved a semi-structured interview with 12 faculty members from a Laotian university as key informants. By using qualitative content analysis, two aspects/components of an individual (lack of team learning, low motivation, limited self-learning, etc.) and organization (unqualified leadership, lack of learning culture, etc.) appear to be significant barriers to workplace learning. Future research may benefit from investigating this area quantitatively